(Learning with a difference )Basic english grammar - Seaton, Anne; Mew, Y. H. (Learners Pub. Singapore, 2001)
Basic English Grammar provides a clear and concise foundation in the essential rules of English grammar, helping learners build confidence and improve their language skills.